A new fuzzy algorithm for delay constrained minimum energy transmission of sensor array data in wireless sensor networks - Verma M.; Shukla K.K. (My University, 2025)
An array of diverse sensors interfaced with a small computing device that has a short-range radio transceiver forms a wireless sensor or node. A network of such devices forms a wireless sensor network (WSN). Today WSNs find application in various fields like battlefield awareness, environmental monitoring, agriculture etc. In this paper, we propose an algorithm that can determine a minimum energy consumption path that also maintains smallest possible end-to-end delay. This will ensure that the data generated by sensor arrays reach their destination in shortest time while consuming minimum energy. The network parameters involved i.e. energy and delay are imprecise in nature, therefore to tackle the prevailing uncertainty, we represent them as trapezoidal fuzzy numbers (TFN) leading to the constrained fuzzy shortest path problem (CFSPP). To solve this problem, we use CoC ranking and demonstrate the effectiveness of the proposed method by simulation analysis. The method proposed in this paper can be integrated with any energy aware WSN protocol. © 2019 Association for Computing Machinery.